IMPLEMENTASI ALIRAN FILSAFAT PENDIDIKAN DALAM KEGIATAN BELAJAR MENGAJAR DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Rahim, Abdur; Ari Eswin, Kembang; Ferdiyana, Ferdiyana; Lisnawati, Lisnawati; Sopyan, Yayan; Fauzi, Ahamd (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to explore the implementation of educational philosophy streams in teaching and learning activities at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The focus of this research includes the application of four main philosophical streams: Essentialism, Perennialism, Progressivism, and Reconstructionism. The research method used is qualitative with a case study approach. Data collection techniques involved in-depth interviews, classroom observation, and documentation. The findings show that Ma’had Al-Zaytun applies an integrated philosophical approach: essentialism and perennialism are reflected in a rigorous curriculum structure and strong moral emphasis, while progressivism and reconstructionism are apparent in adaptive learning strategies that address global social issues. These results highlight how the integration of educational philosophies can shape a holistic and transformative learning environment.